ANALISIS PENGARUH MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPA) “STUDI PADA MAHASISWA STIE SEMARANG PROGRAM STUDI S1 AKUNTANSI” - Heridiansyah, Jefri; SR, Dwi Prawani (JURNAL STIE SEMARANG, 2019)
Competition cannot be avoided anymore, so the quality of graduates of human resources is often questioned in the world of work. Accounting colleges in Indonesia since the late 1980s have been questioned about their reliability in producing financial and business professionals in the face of the 4.0 industrial revolution and the era of economic globalization of the century. PPA is very important for students in accounting study programs because PPA can contribute to becoming a professional accountant. Students' interest in participating in PPA is the interaction of various factors that influence it, one of which is motivation. Based on the test results of "t" of each independent variable (Quality Motivation, Career Motivation and Economic Motivation) it is known that "t" count> "t" table, then Ho is rejected and Ha is accepted which means that there is a positive and significant influence individually. Between independent variables (Quality Motivation, Career Motivation and Economic Motivation) on the dependent variable (Student Interest in PPA). Based on the F test, the F value calculated for F count: 75.337> F table 2.74 with a significance level of 0.000 <0.05, so it can be concluded that the model is a fit model. The coefficient of determination (R2) of 0.759 means that 75.9% of the variation in the dependent variable (Student Interest in PPA) can be explained by independent variables (Quality Motivation, Career Motivation and Economic Motivation).